Temporal and spatial changes of incoming solar short-wave wavelength and long-wave wavelength in the region of Iran - faryad shayesteh; mohammad saligheh; bohloul alijani; amanollah fathnia (تحقیقات کاربردی علوم جغرافیایی)
The smallest change in energy exchange of Earth System Shifts the balance of life. In order to be aware of the solar radiation Balance, Recognition of the measure of Balance level of the input and output components of radiation of input Short wavelength to the surface of the earth and Long Output Wavelength, it is necessary from the earth. To study the energy balance of input and output in Iranian plateau, the input and output radiation data of NCEP / NCAR site was used With a resolution of 2.5 * 2.5 *, including 46 cells in Iran,. For each season, a representative month was considered And correlation, confidence level, coefficient of determination and amount of oscillation of input and output radiation were calculated in different regions of Iran. Finally, some calculations were presented spatially with the IDW method. The results showed that the maximum short-wave wavelength was 230 watts per square meter in August and the lowest was 52 watts per square meter in November. The highest long-wavelength output in August was 65 watts per square meter, and the lowest amount was January and November with 20 watts per square meter. The highest the amount of output increase has been occurred in August in the east of province South Khorasan with a correlation of 0.59 to 112 watts per square meter in 2001. In decreasing output changes, except for May, there was a decrease in the rest of the months. The highest long-wavelength output was in the northwest and in the provinces of Ardabil and Guilan.